PHYTOCHROME B and HISTONE DEACETYLASE 6 Control Light-Induced Chromatin Compaction in Arabidopsis thaliana - Tessadori, Federico (Public Library of Science, 2009)

(untitled)
Natural genetic variation in Arabidopsis thaliana exists for many traits and often reflects acclimation to local environments. Studying natural variation has proven valuable in the characterization of phenotypic traits and, in particular, in identifying genetic factors controlling these traits. It has been previously shown that chromatin compaction changes during development and biotic stress. To gain more insight into the genetic control of chromatin compaction, we investigated the nuclear phenotype of 21 selected Arabidopsis accessions from different geographic origins and habitats. We show natural variation in chromatin compaction and demonstrate a positive correlation with latitude of geographic origin. The level of compaction appeared to be dependent on light intensity. A novel approach, combining Quantitative Trait Locus (QTL) mapping and microscopic examination, pointed at PHYTOCHROME-B (PHYB) and HISTONE DEACETYLASE-6 (HDA6) as positive regulators of light-controlled chromatin compaction. Indeed, mutant analyses demonstrate that both factors affect global chromatin organization. HDA6, in addition, strongly promotes the light-mediated compaction of the Nucleolar Organizing Regions (NORs). The accession Cape Verde Islands-0 (Cvi-0), which shows sequence polymorphism in the PHYB gene and in the HDA6 promotor, resembles the hda6 mutant in having reduced chromatin compaction and decreased methylation levels of DNA and histone H3K9 at the NORs. We provide evidence that chromatin organization is controlled by light intensity. We propose that chromatin plasticity is associated with acclimation of Arabidopsis to its environment. The polymorphic alleles such as PHYB and HDA6 control this process.